A 2010 Legacy Initiative. Driving community participation and the next generation of champions (2010)
Organized sport and physical activity need to be more closely aligned with improved health and social outcomes. The British Columbia Sport Alliance (2010 Legacies Now, Sport BC, Canadian Sport Centre Pacific and BC Games Society) is working to reposition the province`s sport system to maximize strengths that exist and link sport to healthy living outcomes. Canadian Sport Centre Pacific (CSC Pacific) is not only a key contributor in BC, but also within the national sport system through partnerships with Own the Podium and the Canadian Sport Centre Network. Working within the framework and vision of the BC Sport Alliance and in consultation with targeted National and Provincial Sport Organizations, CSC Pacific has developed a plan that will build on the momentum of the 2010 Games and take BC`s high performance sport system to a new level for the benefit of all Canadian athletes. This Legacy Initiative strategy aims to ensure the high performance sport system in BC is armed with a plan supported by expertise and infrastructure that will breed excellence for generations to come.